Geo-temporal provision of pre-hospital emergency anaesthesia by UK Helicopter Emergency Medical Services: an observational cohort study. (May 2020) - Bourn, Sebastian; Turner, Jake; Raitt, James; Tucker, Harriet; ,
Abstract: Background: Pre-hospital emergency anaesthesia (PHEA) is frequently required for injured patients. National Institute for Health and Care Excellence (NICE) quality standards state that PHEA should be delivered within 45 min of an emergency call. We investigated whether there is geo-temporal variation in service provision to the UK population. Methods: We retrospectivly audited the time of day when PHEA is provided by UK Helicopter Emergency Medical Services (HEMS), by recording PHEA provision on a randomly selected week and weekend day in 2018. Pre-hospital emergency anaesthesia in the United Kingdom: an observational cohort study retrospectively assessed the time from emergency call to pre-hospital emergency anaesthesia delivery by HEMS during a 1 yr period from April 2017 to March 2018. The population coverage likely to receive pre-hospital emergency anaesthesia in accord with NICE guidelines was estimated by integrating population data with the median time to PHEA, hours of service provision, geographic location, and transport modality. Results: On a weekday 20 HEMS units (comprising from four to 31 enhanced care teams) were estimated to be able to meet NICE guidelines for delivery of PHEA to a poulation of 6.6–35.2 million individuals (at times of minimum and maximal staffing, respectively). At the weekend, 17 HEMS units (comprising from 5 to 28 enhanced care teams) were estimated to be able to meet NICE guidelines for PHEA deliveryto a population of 6.8–34.1 million individuals (minimum and maximal staffing, respectively). Conclusions: There is marked geo-temporal variation in the ability of HEMS organisations to deliver pre-hospital emergency anaesthesia in the UK.